Cyclic nucleotide signalling in malaria parasites. Issue 12 (20th December 2017) - Baker, David A.; Drought, Laura G.; Flueck, Christian; Nofal, Stephanie D.; Patel, Avnish; Penzo, Maria; Walker, Eloise M.
Abstract : Abstract : The cyclic nucleotides 3′, 5′-cyclic adenosine monophosphate (cAMP) and 3′, 5′-cyclic guanosine monophosphate (cGMP) are intracellular messengers found in most animal cell types. They usually mediate an extracellular stimulus to drive a change in cell function through activation of their respective cyclic nucleotide-dependent protein kinases, PKA and PKG. The enzymatic components of the malaria parasite cyclic nucleotide signalling pathways have been identified, and the genetic and biochemical studies of these enzymes carried out to date are reviewed herein. What has become very clear is that cyclic nucleotides play vital roles in controlling every stage of the complex malaria parasite life cycle. Our understanding of the involvement of cyclic nucleotide signalling in orchestrating the complex biology of malaria parasites is still in its infancy, but the recent advances in our genetic tools and the increasing interest in signalling will deliver more rapid progress in the coming years.